Pengembangan Buku Ajar Tematik Dengan Pendekatan Integrasi Sains Dan Agama Di Kelas 4 Sekolah Dasar Islam Raudlatul Jannah Sidoarjo - Nuzulia, Nuril (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2014)
Purpose of this development is to fulfil the needs of learning material especially in the Islamic Elementary School. In fact, thematic learning separated from religion; therefore continuity of learning model that will be applied is needed. This day, general subject different with religion subject,therefore in this research, researcher integrated between general subjects with religion subject. This development of teaching material is using Dick and Lou Carey model. The result of this development is Thematic Book for student 4th grade of Islamic Elementary School. Product of this development is tested in a series such as: (1) validation of contents, learning design, and learning, (2) Tested on small group and tested on class.Keywords: Development, Teaching Material, Thematic, Integrationbetween Sciences and Religion